Data from: Local distribution patterns of fleshy-fruited woody plants – examining the orchard hypothesis - Matilda Arnell; Johan Ehrlén; Ove Eriksson (Stockholm University, 2020)
This is the data from the article

Local distribution patterns of
fleshy-fruited woody plants – examining the orchard hypothesis (DOI: 10.1111/ecog.05359)

Matilda Arnell, Johan Ehrlén and Ove Eriksson



The study was carried out in the Tullgarn nature reserve
(17°33'45E 58°57'56 N) in the province of Södermanland in Sweden. In the
study area we established 15 sites.

The sites were chosen to cover a range of potential habitats for
fleshy-fruited woody species, and included those that were a priori expected as
favourable habitats, e.g. forest edges, and less favourable habitats, e.g.
within forests dominated by coniferous species (Picea abies and Pinus
sylvestris). At the 15 sites we established three plots per site (45 plots)
and at each plot we established subplots for the seedling recruitment
experiment.



Study design

In 50 m radius circles at one of the three plots at each site we mapped
all individuals of the local guild of fleshy-fruited woody trees and shrubs and
recorded their height (or diameter at breast height) and reproductive status.
This data is found in “spatial data_Arnell et al 2020.csv”. Please consult the
readme-file for further details.



In 50 m radius circles surrounding all three plots at each site we
recorded presence/absence of reproductive individuals (displaying flowers or
fruits) for the species included in the seedling recruitment experiment. This
data is found in “plot scale data_Arnell et al 2020.csv”. Please consult the
readme-file for further details.



Seedling recruitment experiment

At each plot, in subplots of 50 × 50 cm, we sowed 50 seeds of each of
ten species of the local guild (figure 2A). The species were: Crataegus laevigata, Frangula alnus, Juniperus communis, Lonicera
xylosteum, Prunus avium, Prunus padus, Prunus spinosa, Ribes
alpinum, Rubus idaeus and Sorbus
aucuparia. The seeds were gathered from fruits collected in the peak of the
fruiting season of each species (mainly July-August, but October for J. communis, S. aucuparia and P. spinosa).
We removed the pulp and allowed the seeds to dry in room temperature.



The experiment was initiated in the autumn of 2015. In 2016 and 2017, we
recorded seedlings on three occasions each year, between early June and early
September. In 2018, we recorded seedlings and small juveniles once in June. At
each occasion, the location of all seedlings was noted and used to identify
individual recruits, and allowing us to identify new seedlings. All recruits
were followed throughout the survey period. At all occasions, we also searched
for seedlings of the study species in control plots (where no seeds were added)
located adjacent to the sowing plots.

The data from the seedling recruitment experiment
is found in “plot scale data_Arnell et al 2020.csv”. Please consult the
readme-file for further details.

Spatially explicit patterns of associations

Using the mapped positions of all individuals from the 50 m radius
circles (spatial data_Arnell et al 2020.csv), we investigated distribution
patterns by performing four different point pattern analyses. The analyses were
performed in the software PROGRAMITA (Wiegand and Moloney 2014).

Data
reconfigured to be compatible with PROGRAMITA can be found in “data_PROGRAMITA.zip”.



Please contact Matilda Arnell (matilda.arnell@su.se) for information or
collaboration.



Please cite also the original article when using these data (DOI: 10.1111/ecog.05359).
Keywords: Ecology; 50202 Conservation and Biodiversity; Ecology; Ekologi